1976
DOI: 10.1126/science.1251197
|View full text |Cite
|
Sign up to set email alerts
|

Surface Predominance of Trace Elements in Airborne Particles

Abstract: A number of minor and trace elements including Be, C, Ca, Cr, K, Li, Mn, Na, P, Pb, S, Tl, V, and Zn present in coal fly ash are found to be preferentially concentrated on the particle surfaces. Environmentally effective concentrations of these elements are thus much higher than indicated by conventional bulk analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0
4

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(116 citation statements)
references
References 6 publications
6
106
0
4
Order By: Relevance
“…148,152 The concentration of the trace elements within the submicrometer and supramicrometer ash fraction increases with decreasing particle size. 73,88 • The surfaces of the ash particles are also enriched in volatile elements relative to their core. 88 • The major influence on the fraction of ash that is vaporized is the temperature.…”
Section: Coal-fired Steam Generation Boilersmentioning
confidence: 99%
See 2 more Smart Citations
“…148,152 The concentration of the trace elements within the submicrometer and supramicrometer ash fraction increases with decreasing particle size. 73,88 • The surfaces of the ash particles are also enriched in volatile elements relative to their core. 88 • The major influence on the fraction of ash that is vaporized is the temperature.…”
Section: Coal-fired Steam Generation Boilersmentioning
confidence: 99%
“…Studies using surface spectroscopic techniques have shown that the surface layers of both the supermicron 88 and submicron 21 ash particles are enriched in the trace elements. By ion milling of the particles, one can show the stratification that results from the sequential deposition of elements.…”
Section: Particle (Soot) Inception By Chemical Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, from the combustion of nearly 600 millions tons of coal per year in the U. S., it is estimated that thousands of tons of.potentially hazardous trace elements are released into the environment each year (Harvey et al, 1983;Akers, 1989). The airborne particulates that escape the post-combustion cleaning processes are respirable particles having an enriched concentration of trace elements on their surfaces (Natusch et al, 1973;Linton et al, 1976). As a result, the U. S. government is expected to place limits on trace element emissions as part of the Clean Air Act Amendment.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Recent results (30) have established that a number of trace elements, including several potential carcinogens are more highly concentrated on the surfaces of coal fly ash particles than in their interior. This phenomenon is probably due to particle surface deposition of elements volatilized during combustion and is found to occur for particles derived from a variety of high temperature combustion or smelting operations, e.g., automobile exhaust particulates and blast furnace dusts (31).…”
Section: Surface Association Of Trace Elementsmentioning
confidence: 99%